(3cJGH GdQhM (B/s - (3GHf bje GdLhRjI, eMeO Hf CHj HcQ Hf CjhHs 691-751 (3gLQjs; (3GdEUdGMj, eMeO CLed CjhHs 1953-; (3bGdej, ceGd Hf eMeOs ((3ecI GdecQeI (B:s (3OGQ YGde GdahGFO ddfTQ hGdJhRjY ,s, 2011)
(3GdYbjOI(B-(3GdSeYjGJ(B-(3GdQhM(B.s
Keywords: (3GdSeYjGJs -- (3GdQhMs; (3GdZjHjGJs -- (3GdQhMs